Jamie does, Spain, Italy, Sweden, Morocco, Greece, France : easy twists on classic dishes inspired by my travels - Oliver, Jamie, 1973- (Michael Joseph, 2010)
Jamie Does . . .is Jamie's personal celebration of amazing food from six very different countries. Cheap, short-haul flights and long weekend getaways have become increasingly popular and within a few short hours of the UK there are new and exciting worlds of food waiting to be discovered as Jamie finds out. Each chapter focusses on a different city or region - Marrakesh, Athens, Venice, Andalucia, Stockholm and the Midi Pyrenees region of France. Classic recipes sit alongside new dishes that Jamie learns along the way. Alongside each recipe there is a beautiful photograph of the finished dish, as well as incredible reportage shots of Jamie's experiences in each country.Jamie says- 'The food I've embraced on each trip is a mixture of what you could call the cliched star dishes - the many tagines of Morocco, the flamboyant paellas of Spain, the comforting risottos from Italy and the zingy fresh flavours of a classic Greek salad - and the recipes that I've been inspired to make after walking through the markets and soaking up the vibes of each place. What you'll find in this book is fun, optimistic, escapist food you can actually cook and enjoy in your own home.